Profit and punishment: how America criminalizes the poor in the name of justice - Messenger, Tony (St. Martin's Press, 2021)
"In Profit and Punishment, a Pulitzer Prize-winning journalist exposes the tragedy of modern-day debtors prisons, and how they destroy the lives of poor Americans swept up in a system designed to penalize the most impoverished. "His Pulitzer Prize winning series on debtors' prisons in Missouri made a serious difference in real people's lives and his book will be a must read for a nation seeking a bipartisan path forward on criminal justice reform." -Claire McCaskill, former US Senator and analyst for MSNBC As a columnist for the St. Louis Post-Dispatch, Tony Messenger has spent years in county and municipal courthouses documenting how poor Americans are convicted of minor crimes and then saddled with exorbitant fines and fees. If they are unable to pay, they are often sent to prison, where they are then charged a pay-to-stay bill, in a cycle that soon creates a mountain of debt that can take years to pay off. These insidious penalties are used to raise money for broken local and state budgets, often overseen by for-profit companies, and it is one of the central issues of the criminal justice reform movement. In the tradition of Evicted and The New Jim Crow, Messenger has written a call to arms, shining a light on a two-tiered system invisible to most Americans. He introduces readers to three single mothers caught up in this system: living in poverty in Missouri, Georgia, and South Carolina, whose lives are upended when minor offenses become monumental financial catastrophes. As these women struggle to clear their debt and move on with their lives, readers meet the dogged civil rights advocates and lawmakers fighting by their side to create a more equitable and fair court of justice. In this remarkable feat of reporting, Tony Messenger exposes injustice that is agonizing and infuriating in its mundane cruelty, as he champions the rights and dignity of some of the most vulnerable Americans."